A novel hypothesis for the formation of conoidal projectile wounds in sandwich bones - Rickman, John M.; Shackel, James (Springer, 2018)
When perforated by a projectile, sandwich bones typically exhibit wounds with a distinct conoidal morphology that is widely utilised both in wound diagnosis and trajectory determinations. However, the dynamic fracture mechanisms underlying this intriguing wound type have yet to be experimentally verified. The most frequently quoted hypothesis for their formation, plug and spall, is difficult to reconcile with the conoidal morphology exhibited by such wounds. The present article carries out a high-speed videographic and micro-computerised tomographic (μ-CT) analysis of perpendicularly produced projectile wounds induced from 139.15 to 896.84 metres per second (m/s) in pig scapulae. Fundamental data on energy absorption, wound shape and bevel symmetry are presented. Cross-sectional fracture morphology revealed by μ-CT raises the novel hypothesis that tensile stresses induced by the projectile in the outer cortex elicit cone crack formation and that this cone crack then propagates catastrophically through the entire sandwich structure. This process results in the momentary formation of a bioceramic conoid, a conoidal volume of bone consisting of all three sandwich bone layers separated from the parent bone by the internal bevel. Fragmentation of the separated volume leaves the conoidal wound behind as its counterpart. The significance of this hypothesis in terms of differential diagnosis and interpretation of bevel shape is discussed.
Keywords: Skeletal trauma; Projectile injuries; Forensic anthropology; Forensic pathology; Fracture; Sandwich bones